Diet selectivity in a terrestrial forest invertebrate, the Auckland tree wētā, across three habitat zones. Issue 5 (1st February 2018) - Brown, Matthew B. G. J.; Gemmill, Chrissen E. C.; Miller, Steven; Wehi, Priscilla M.
Abstract: Insects are important but overlooked components of forest ecosystems in New Zealand. For many insect species, information on foraging patterns and trophic relationships is lacking. We examined diet composition and selectivity in a large‐bodied insect, the Auckland tree wētā Hemideina thoracica, in three habitat zones in a lowland New Zealand forest. We asked whether H. thoracica selectively forage from available plant food sources, and whether these choices were lipid‐rich compared to nonpreferred available plants. We also identified the proportion of invertebrates in their frass as a proxy for omnivory. From reconnaissance plot sampling, together with fecal fragment analysis, we report that more than 93% of individual tree wētā had eaten invertebrates before capture. Additionally, wētā in the highest elevation hillslope habitat zone consumed significantly fewer species of plants on average than wētā on the low‐elevation terrace habitat. Upper hillslope wētā also had the highest average number of invertebrate fragments in their frass, significantly more than wētā in the low‐elevation terrace habitat zone. Wētā showed high variability in the consumption of fruit and seeds across all habitat zones. Generally, we did not observe diet differences between the sexes (although it appears that male wētā in the mid‐hillslope habitat ate fruits and seeds more voraciously than females), suggesting that the sexes have similar niche breadths and display similar degrees of omnivorous behavior. Extraction of leaf lipids demonstrated a range of lipid content values in available plants, and Ivlev's Electivity Index indicated that plant species which demonstrated high electivity tended to have higher concentrations of lipids in their leaves. Our findings indicate that H. thoracica forage omnivorously and selectively, and hence play multiple roles in native ecosystems and food webs. Abstract : Tree wētā are eating selectively across zones based on lipid content of native plants. In the terrace, wētā are eating significantly more plant species than the other two zones. The trend is for wētā to eat more invertebrates as elevation increases. Mid‐hillslope wētā appear to eat more fruits and seeds, but this is driven by a couple of male individuals.